Morning appointment time rather than training load affects sleep during a training camp in young elite Rugby Union players - Chauvineau, M.; Mathieu, B.; Boissard, G.; Piscione, J.; Duforez, F.; Guilhem, G.; Nedelec, M. (European Journal of Sport Science, 2025)
This investigation aimed to evaluate sleep of young rugby union players during a 10-day training camp accounting for the potential influence of prior daily training load and the morning appointment time. Twenty-six elite male under-20 rugby union players were monitored each day during a 10-day training camp including two exhibitions matches. Sleep-wake patterns and sleep architecture were assessed using actigraphy and a reduced-montage dry-electroencephalographic headband device, respectively. Training load and perceived wellness were, respectively, evaluated using GPS trackers and 10-score visual analogue scales. The prevalence of nights with sleep duration < 7 h, wake after sleep onset > 40 min and sleep efficiency < 85% was 30.3%, 77.8% and 43.4%, respectively. Every 100-m increase in high-speed running distance increased sleep duration (ß = +4.9 min, p < 0.05) and reduced the number of sleep stage shifts (ß = -1.1, p < 0.05). The shortest sleep duration (06:52 ± 00:34 h) occurred on the day of Match 1, when the morning appointment was the earliest, that is, 7:30. Sleep duration (-19.3 min, p = 0.01) and efficiency (-2.2%, p < 0.01) were impaired when the morning appointment was scheduled at 8:30 compared to 8:00. This study supports that the training camp is a vulnerable period for sleep, but a controlled, non-excessive training load promotes sleep quantity and continuity of sleep architecture. The organisational aspects of the camp strongly influence the sleep-wake patterns. Coaches should be aware of the putative impact of earlier and/or unusual morning appointment times on sleep, especially in proximity to a match.